Correlation between lower limb bone morphology and gait characteristics in children with spastic diplegic cerebral palsy. - Carriero, A; Zavatsky, A; Stebbins, J; Theologis, T; Shefelbine, S (2009)
BACKGROUND: Children with spastic diplegic cerebral palsy (CP) exhibit abnormal walking patterns and frequently develop lower limb, long bone deformities. It is important to determine if any relationship exists between bone morphology and movement of the lower limbs in children with CP. This is necessary to explain and possibly prevent the development of these deformities. METHODS: This study investigated the relationship between bone morphology and gait characteristics in 10 healthy children (age range, 6-13 years; mean, 8 years 7 months; SD, +/-2 years 7 months) and 9 children with spastic diplegic CP (age range, 6-12 years; mean, 9 years 2.5 months; SD, +/-1 year 10.5 months) with no previous surgery. Three-dimensional magnetic resonance images were analyzed to define bone morphology. Morphological characteristics, such as the bicondylar angle, neck-shaft angle, anteversion angle, and tibial torsion, were measured. Gait analyses were performed to obtain kinematic characteristics of CP and normal children's gait. Principal component analysis was used to reduce the dimensionality of 27 parameters (26 kinematics variables and age of the children) to 8 independent variables. Correlations between gait and bone morphology were determined for both groups of children. RESULTS: Results indicated that in healthy children, hip adduction was correlated with neck-shaft and bicondylar angles. In CP children, pelvic obliquity correlated with neck-shaft angle, and foot rotation with bicondylar angle. In the transverse plane, hip and pelvic rotational kinematics were related to femoral anteversion in healthy children and to tibial torsion in CP children. CONCLUSION: Different development was observed in femoral and tibial morphology between CP and healthy children. The relationship between bone shape and dynamic gait patterns also varied between these populations. This needs to be taken into account, particularly when surgical treatment is planned. CLINICAL RELEVANCE: Understanding the relationship between gait abnormality and bone deformity could eventually help in developing treatment regimens that will address gait deviations at the correct level and promote normal bone growth in children with CP.